Atlas of radiographic features of osteoarthritis of the ankle and hindfoot. Issue 12 (December 2015) - Kraus, V.B.; Kilfoil, T.M.; Hash, T.W.; McDaniel, G.; Renner, J.B.; Carrino, J.A.; Adams, S.
Summary: Objective: To develop a radiographic atlas of osteoarthritis (OA) for use as a template and guide for standardized scoring of radiographic features of OA of the ankle and hindfoot joints. Method: Under Institutional Review Board approval, ankle and hindfoot images were selected from a cohort study and from among cases that underwent ankle radiography during a 6-month period at Duke University Medical Center. Missing OA pathology was obtained through supplementation of cases with the assistance of a foot and ankle specialist in Orthopaedic surgery and a musculoskeletal radiologist. Images were obtained and reviewed without patient identifying information. Images went through multiple rounds of review and final images were selected by consensus of the study team. For intra-rater and inter-rater reliability, the kappa statistic was calculated for two readings by three musculoskeletal radiologists, a minimum of two weeks apart, of ankle and hindfoot radiographs from 30 anonymized subjects. Results: The atlas demonstrates individual radiographic features (osteophyte and joint space narrowing (JSN)) and Kellgren–Lawrence grade for all aspects of the talocrural (ankle joint proper) and talocalcaneal (subtalar) joints. Reliability of scoring based on the atlas was quite good to excellent for most features indicated. Additional examples of ankle joint findings are illustrated including sclerosis, os trigonum, subchondral cysts and talar tilt. Conclusions: It is anticipated that this atlas will assist with standardization of scoring of ankle and hindfoot OA by basic and clinical OA researchers.